English Schools with a Religious Ethos: For a Re-Interpretation of Religious Autonomy - Hunter-Henin, Myriam (Religion and human rights, 2018)
Rooted in a principle of non-interference in matters of religious beliefs, supported by an ideology of parental school choice, faith state schools in England have enjoyed a large discretion to promote their religious ethos. Recent judicial and legislative interventions into the affairs of religious schools may be criticized as they betray these philosophical roots, without offering an alternative coherent justificatory model for law and religion relationships. By seeking to remove the allegedly socially or racially divisive edge of religious autonomy, these interventions have provoked an unwarranted and inconsistent mingling of the secular and the religious. Moreover, they have imposed a form of state governance which has reinforced religious authorities to the detriment of the autonomy of local stakeholders, parents and schools. It is claimed that a more deliberative and contextual re-interpretation of the principle of religious autonomy in English law would lead to less confrontational and more acceptable outcomes.